Pemodelan dan Dampak Pembelajaran pada Materi Gerak Jatuh Bebas di Berbagai Jenjang Pendidikan: Kajian Meta-Analisis - Akhlis, Isa; Ome, Yunita Dwi Saputri; Nisa, Maulidia Khoirun (Universitas PGRI Semarang, 2024)
This study aims to analyse modelling and learning effects in the topic of free fall motion through a meta-analysis approach. This study covers the distribution of research based on education level, learning method, and learning effect over a period of time. The analysis shows that high school dominates the distribution of research, followed by university, while primary and junior high school have lower representation. In terms of learning methods, experimentation is the most frequently used approach, followed by simulation, mathematical modelling, problem-based learning, and thought experiments. Meanwhile, the most dominant learning effects were improved conceptual understanding, followed by technological skills, collaboration and critical thinking, and practical relevance. This research highlights the importance of technology and activity-based approaches in supporting students' understanding of the concept of free fall motion. In addition, the need to extend the research in early primary and secondary education is important to build a strong conceptual foundation early on. The results of this study are expected to provide insights for the development of more adaptive and relevant learning strategies at various levels of education.